The micro level of reading miscues: case studies of six learners - Huszti Ilona; Густі Ілона (Language Pedagogy PhD Programme, Eötvös Loránd University, 2008)
Abstract. The present paper aims to report six case studies of six Transcarpathian Hungarian learners—three successful readers and three unsuccessful ones—when reading aloud in English as a foreign language. The study described in this article is part of a large-scale investigation into the quality and quantity of reading miscues made by non-native readers during oral reading. Findings suggest that both successful and unsuccessful readers make substitution miscues most frequently, and these miscues resemble the Expected Response (ER)—i.e. the printed text—grapho-phonemically. However, weak readers make more miscues than strong readers.
Keywords: reading aloud; oral reading; strong readers; weak readers; reading miscues